The efficacy of SPORT TM as a dietary supplement on performance and recovery in trained athletes - Timmons, B. W.; Newhouse, I. J.; Thayer, R. E.; McAuliffe, J. E; McIllwaine,St. (Canadian Journal of Applied Physiology, 2000)
This study investigated the efficacy of SPORTTM (a popular dietary supplement) in improving performance and assisting recovery in 9 trained athletes. In a double-blind, crossover experiment, subjects ran at workloads of 60 and 80% of peak oxygen uptake (PeakVO2) for 5 min each with 5 min recovery after each bout and at 100% PeakVO2 until exhaustion. Two capsules of either SPORTTM or a gelatin placebo were administered 1 hr prior to exercise and immediately after each workload. Heart rate (HR) and blood lactate (BLa) were measured at 1 hr prior to exercise, immediately after the 100% exercise bout and at 5, 10, 20, and 45 min during recovery. No significant differences between treatments on HR and BLa measures at any of the 6 time periods, or on subject's time to exhaustion were found. Under the conditions of this experimental design, SPORTTM had no beneficial effects on performance or recovery in trained athletes.